Isolation and structural elucidation of bioactive obovatol dimeric neolignans from the bark of Magnolia officinalis var. biloba. (February 2022) - Xu, Kailing; Ma, Jie; Li, Chuan; Li, Chuangjun; Zang, Yingda; Sun, Xingyan; Chen, Xiaoguang; Wang, Xiaoliang; Zhang, Dongming
Abstract: (+)/(−)-Diobolignans A–F, six pairs of enantiomeric obovatol dimeric neolignans, were isolated from the bark of Magnolia officinalis var. biloba . (+)/(−)-Diobolignans A to C possessed a dioxane ring between the benzene ring and the propyl side chain, while (+)/(−)-diobolignans D to F possessed a furan ring. Meanwhile, (+)/(−)-diobolignans B and C, as well as (+)/(−)-diobolignans E and F, were two epimeric pairs of enantiomers, respectively. Their structures were determined by extensive analyses of HRESIMS, UV, IR, NMR and electronic circular dichroism (ECD) calculations. The bioassay showed (+)-diobolignan A displayed cytotoxic activities against human cancer cell lines HGC27 and HT29 with the IC50 values of 9.43 and 9.45 μ M, respectively. In addition, (−)-diobolignan A and (±)-diobolignan E showed neuroprotective effect on glutamic acid-induced cellular damage in SK-N-SH cell. Graphical abstract: Undescribed dimeric neolignans were isolated from the bark of Magnolia officinalis var. biloba . Some of compounds exhibited cytotoxic or neuroprotective activities. Image 1 Highlights: Undescribed obovatol dimeric neolignans were isolated from the bark of Magnolia officinalis var. biloba. The structures were determined by spectroscopic techniques, and ECD calculations. (+)-Diobolignan A displayed cytotoxic activities against human cancer cell lines HGC27 and HT29. (−)-Diobolignan A showed neuroprotective effect on glutamic acid-induced cellular damage in SK-N-SH cell.